Global tendencies and frontier topics in hemodynamics research of intracranial aneurysms: a bibliometric analysis from 1999 to 2022 - Chen, Bo; Huang, Siting; Zhang, Liyang; Yang, Liting; Liu, Yuanyuan; Li, Chuntao (Frontiers in Physiology, 2023)
Background: Hemodynamics plays a crucial role in the initiation, enlargement, and rupture of intracranial aneurysms (IAs). This research aimed to map the knowledge network of IA hemodynamic research through a bibliometric analysis. Methods: Publications regarding hemodynamics in IAs from 1999 to 2022 were retrieved from the Web of Science Core Collection (WoSCC). The contributions of countries, institutions, authors, and journals were identified by VOSviewer, Scimago Graphica, and Microsoft Excel. The tendencies, frontier topics, and knowledge networks were analyzed and visualized by VOSviewer and Citespace. Results: We collected a total of 2226 publications in the field of IA hemodynamics. The number of annual publications showed an overall upward tendency. Among these, the USA, Japan, and China were the 3 major contributing countries. Capital Medical University, SUNY Buffalo University, and George Mason University were the 3 top productive institutions. Meng H ranked first in prolific and highly cited authors, and Cebral JR took the lead in the co-cited authors. American Journal of Neuroradiology was the top first journal in the number of publications, citations, and co-citations. Besides, research topics can be mainly divided into 3 clusters: hemodynamics itself, its relationship to IA rupture, and its relationship to IA treatment. Frontier directions included flow diverter, complication, morphology, prediction, recanalization, 4D flow MRI, and others. Conclusion: This research drew the knowledge map of the top countries, institutions, authors, publications, and journals in IA hemodynamics over the past two decades. Current and future hotspots of IA hemodynamics mainly include the hemodynamics itself (4D flow MRI), its relationship to IA rupture (morphology and prediction), and its relationship to IA treatment (flow diverter, complication, and recanalization).